The effectiveness of a community-based exercise program on depression symptoms among people living with HIV. Issue 3 (4th March 2021) - Sousa, Caio V.; Lewis, John E.; Simoes, Herbert G.; Campbell, Carmen S. G.; Zaldivar, Sarah; Rodriguez, Allan; Woolger, Judi; Konefal, Janet; Tiozzo, Eduard
ABSTRACT: HIV is a worldwide public health issue affecting millions of individuals, and people living with HIV (PLWH) are often affected by depression. Nonetheless, exercise can prevent and treat depression among PLWH. The aim of the present study was to investigate the effect of exercise on depression symptoms in PLWH. Using a prospective single-arm trial, a semi-supervised community-based exercise intervention was offered 3 times/week for 12 weeks to PLWH (n = 52; age: 49 ± 6 years; HIV diagnosis: 19 ± 15 years). Participants were divided into compliant (≥1 exercise session/week) and non-compliant (<1 exercise session/week) groups according to their attendance in the intervention. Depression symptoms were assessed using the Beck Depression Inventory (BDI), and the change in BDI from baseline to post-intervention was assessed with an analysis of covariance, adjusted for demographics. The post-intervention BDI score was significantly lower (p = 0.027) for the compliant group compared to the non-compliant group, and the rate of improvement from moderate/severe symptoms of depression to minimal symptoms of depression was four times greater in the compliant group. In conclusion, a community-based exercise program may be effective in reducing depression symptoms among PLWH.